POTENSI MELEMAHNYA PRINSIP TERBUKA DAN BERSAING DALAM PENGADAAN DENGAN METODE E-PURCHASING - Bintang Puwan Permata (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2024)
E-purchasing is a form of government innovation aimed at expediting the procurement process for goods and services. However, in its implementation, the competition among participants/providers of goods/services appears to be superficial. This research aims to review the application of the principles of openness and competitiveness in the procurement of goods and services using the e-purchasing method. This study is a normative legal research with a prescriptive nature and a legislative approach. Data collection is conducted through a literature study technique. The types of data used are secondary data in the form of primary legal materials and secondary legal materials. The data obtained are analyzed using deductive reasoning techniques. Based on the research findings, it is known that there is a potential for collusion that results in unhealthy business competition in the implementation of the procurement of goods and services through the e-purchasing method. Therefore, there is a need for regulations that clearly define the requirements and criteria for the selection of goods/services providers